Optimizing Digital Literacy in Increasing Competitive Advantage and Corporate Performance - Rachmadi, Moch Faizal; Prajanti, Sucihatiningsih Dian Wisika (Fakultas Ekonomi, Universitas Negeri Semarang, 2023)
Business units such as cooperatives are currently experiencing growth along with developments in the era of the industrial revolution 4.0. Today's era also requires business actors, including cooperatives, to continue to be able to transform digitally in various ways. The main problem currently being faced by cooperative actors is the low competence of Human Resources (HR) in mastering digital literacy skills related to effective and efficient management of production operations starting from production, accounting, marketing, management and so on. These problems must be addressed and dealt with appropriately, quickly and sustainably (sustainability). This digital literacy capability makes a major contribution in optimizing the competitive advantage and corporate performance of cooperatives, especially in today's digital era. Based on these problems, the purpose of this research is to study and optimize digital literacy in increasing competitive advantage and sustainable cooperative performance in the Koperasi Produsen Petani Indonesia (KPPI). The urgency of this research is that cooperative actors have literacy skills, business models and sustainable management patterns (sustainability) based on digital technology. The research methodology is a qualitative approach using interviews, observation, documentation, demonstrations and Focus Group Discussion (FGD) techniques. The research stages include introduction, implementation and evaluation.